L-cysteine biosynthesis in Bacillus subtilis: identification, sequencing, and functional characterization of the gene coding for phosphoadenylylsulfate sulfotransferase. - Mansilla, M C (1997)
Random Tn917 mutagenesis of Bacillus subtilis followed by selection of lipoic acid auxotrophs led to the isolation of the cysH gene. The gene was sequenced and found to encode a phosphoadenylylsulfate sulfotransferase with a molecular mass of 27 kDa. Expression of lacZ fused to the cysH promoter was repressed by cysteine and sulfide and induced by sulfur limitation, indicating that cysH is controlled at the level of transcription.